Agile maturity model: analysing agile maturity characteristics from the SPICE perspective. Issue 5 (24th October 2013) - Schweigert, Tomas; Vohwinkel, Detlef; Korsaa, Morten; Nevalainen, Risto; Biro, Miklos; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
Abstract The paper discusses structure, quality and content of the currently available agile maturity models. It presents two approaches on how to deal with such models. As a first step of the analysis, the paper contains a compilation of maturity level naming used by these agile maturity models because the variety of level naming is a sign of the variety of understanding and of definition of agile maturity. While many papers deal with agile from an inside perspective, this paper is written from the perspective of Software Process Improvement (SPI) and Capability Determination, the European Certification and Qualification Association PI Manager Certification Scheme and also the SPI Manifesto. The paper does not explicitly present its own agile maturity model. The analysis approaches presented in the paper show that the currently available agile maturity models are not fit for industrial use. The synthesis of an acceptable model seems to be feasible as the analysed models address typical organisational processes including life cycle management. Copyright © 2013 John Wiley & Sons, Ltd.